Effects of maternal hyperthermia on neurodevelopment: a literature review - Barootkoob, Behsheed; Rahimi, Parya; El-Hashash, Ahmed (International Journal of Research in Medical Sciences, 2023)
Maternal hyperthermia, defined as a body temperature above 38°C (100.4°F) is due to various etiologies during pregnancy, and has been a subject of growing research interest. This phenomenon is considered a potential environmental teratogen contributing to the development of neural tube defects (NTDs) and other neurodevelopmental disorders. NTDs such as anencephaly and spina bifida, are known to be multifactorial in origin, resulting from a complex interplay between genetic and environmental factors. In this review, we aim to comprehensively analyze the effect of maternal hyperthermia on neurodevelopmental disorders and associated congenital anomalies. In addition, we will highlight both the infectious and noninfectious causes of maternal hyperthermia, as well as any risks and potential preventive measures. The literature search identified studies reporting associations between maternal hyperthermia and adverse fetal outcomes. We have evaluated the link between maternal fever due to infections during pregnancy and the increased likelihood of NTDs, particularly anencephaly and spina bifida, as well as Neurodevelopmental disorders. ​​In addition, the effects of non-infectious causes of maternal hyperthermia, including exercise and exposure to heat sources like saunas and hot tubs, on neurodevelopment have also been studied with varying degrees of evidence. Maternal hyperthermia elevates the risk of NTDs and neurodevelopmental disorders in infants, with folic acid offering partial protection, while other factors elevate this risk. However, further research is needed to define the precious association of these factors.